Bersiul Sebagai Bentuk Kekerasan Seksual: Nalar Sadd al-Żarī’ah Dalam Hukum Positif di Indonesia (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2023)
Whistling, initially regarded as a harmless personal expression, has evolved over time to be considered a form of sexual violence in specific legal and interpretative contexts. Consequently, Indonesian law has incorporated this activity as one manifestation of sexual violence. This article aims to provide an analysis and elucidation of legislative regulations pertaining to sexual violence, which includes whistling as a form thereof, utilizing the sadd al-dzari’ah or preventive logic approach. Employing a document analysis methodology, the study focuses on Law Number 12 of 2022, Minister of Education and Culture Regulation Number 30 of 2021, and Minister of Religious Affairs Regulation Number 73 of 2022 as its study objects. The research reveals that the inclusion of whistling as a form of sexual violence in legislative regulations is substantiated not only by various social facts but also by the presence of preventive reasoning within sadd al-dzari’ah. This suggests that whistling is perceived to potentially lead to more serious offenses, both in terms of fostering a continuous inclination to engage in such behavior and escalating its frequency and intensity, as well as instigating a profound sense of intimidation and serious degradation for the victims.